METHODOLOGICAL BASES OF MECHANISM OF CREATION OF IMAGE OF NATIONAL TOURISM PRODUCT IN GLOBALIZATION CONDITIONS - Kovalska, Lesia; Tkachenko, Tetyana; Kovalska, Anzhela (Mountain School of Ukrainian Carpaty, 2018)
The article outlines the preconditions for the formation of a positive image of a tourist product, which influences the increase of the authority of the state on the international level, increase of tourist flows, promotion of investment inflow, development of tourist and recreational infrastructure, increase of the general level of economic development and welfare of the population. It is revealed that in order to determine the "tourist magnet" for visitors it is necessary to take into account the completeness of the tourist product filling, which reflects the state, content and structure of the tourist and recreational potential of the country. It is also noted that the image affects the formation and attractiveness of the tourist destination for recreation, namely: health improvement, treatment, travel, etc. To cover the main provisions of the article, complex and historical approaches are used with the use of general scientific research methods: empirical (observation, experiment, description, comparison), empirical-theoretical (analysis and synthesis, induction and deduction, approach), theoretical (formalization, definition, description, etc). It was established that the perception of the tourist image is influenced by rational requirements, interests, stereotypes, socio-cultural features of mass consciousness. In addition, by its nature, tourism has a figurative character - it's memories, associations, representations that are caused by mentioning a certain country as a tourist object. The image exists autonomously from state or other structures that are interested in its positive formation. The main difference between the image of the vision is that the image is constructed purposefully and consciously, while the vision is formed independently, naturally. It is proved that the formed positive image of the national tourist product, is associated with a high level of attractiveness, aesthetics, comfort, safety, the possibility of implementing a variety of tourist practices. To objectively assess the level of attractiveness of the image, it is necessary to establish the estimated indicators, of which the main groups are: psychophysical, social, reputation, cultural-aesthetic, and economic. Taking into account the particularities of the tourism industry, namely: the priority of the wishes of the consumers, the primacy and uniqueness of the tourist service, the extremely important role of marketing in the industry, as well as the integrated structure of the national tourist product on the basis of the WTO classification and the concept of the territorial tourism product. Such a structure should include the following components: tourist and recreational resources and services, including goods; related products and services; organizational, legal and socio-political environment of tourism; personnel potential of the country; infrastructure; marketing.